Alternative Complement Pathway Inhibition Abrogates Pneumococcal Opsonophagocytosis in Vaccine-Naïve, but Not in Vaccinated Individuals - Muri, Lukas; Ispasanie, Emma; Schubart, Anna; Thorburn, Christine; Zamurovic, Natasa; Holbro, Thomas; Kammüller, Michael; Pluschke, Gerd (Frontiers in Immunology, 2021)
To assess the relative contribution of opsonisation by antibodies, classical and alternative complement pathways to pneumococcal phagocytosis, we analyzed killing of pneumococci by human blood leukocytes collected from vaccine-naïve and PCV13-vaccinated subjects. Two different physiologic opsonophagocytosis assays based on either hirudin-anticoagulated whole blood or on washed cells from EDTA-anticoagulated blood reconstituted with active serum, were compared. Pneumococcal killing was measured in the presence of inhibitors targeting the complement components C3, C5, MASP-2, factor B or factor D. The two assay formats yielded highly consistent and comparable results. They highlighted the importance of alternative complement pathway activation for efficient opsonophagocytic killing in blood of vaccine-naïve subjects. In contrast, alternative complement pathway inhibition did not affect pneumococcal killing in PCV13-vaccinated individuals. Independent of amplification by the alternative pathway, even low capsule-specific antibody concentrations were sufficient to efficiently trigger classical pathway mediated opsonophagocytosis. In heat-inactivated or C3-inhibited serum, high concentrations of capsule-specific antibodies were required to trigger complement-independent opsonophagocytosis. Our findings suggest that treatment with alternative complement pathway inhibitors will increase susceptibility for invasive pneumococcal infection in non-immune subjects, but it will not impede pneumococcal clearance in vaccinated individuals.